Prealgebra and introductory algebra with P.O.W.E.R. learning - Messersmith, Sherri (McGraw-Hill, 2014)
Operations with integers; Expressions and equations; Operations with signed fractions; Basic geometry concepts and algebra; Signed decimals; Ratios, rates, and proportions...